2022
DOI: 10.1039/d2lc00665k
|View full text |Cite
|
Sign up to set email alerts
|

Non-adhesive contrast substrate for single-cell trapping and Raman spectroscopic analysis

Abstract: Droplet splitting by exploiting the tailored surface wettability is emerging as an important pathway to create the ultralow volume of samples that can find applications in bioassays, tissue engineering, protein...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The exposure of oxygen plasma onto the cleaned quartz surface results in the formation of −OH groups on the surface and makes them highly hydrophilic (with a water contact angle, WCA ∼ 0°). The −OH bonds on the quartz surface facilitate the grafting of silicone oil onto the surface via hydrolysis and condensation reactions. , As a result of oil grafting, the hydrophilic quartz becomes hydrophobic with a nonadhesive behavior toward the water. The equilibrium water contact angle (WCA) of a 10 μL droplet on the oil-grafted surface is measured to be ∼107 ± 2°, as compared with the pristine quartz that exhibits a WCA of 58 ± 2° (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The exposure of oxygen plasma onto the cleaned quartz surface results in the formation of −OH groups on the surface and makes them highly hydrophilic (with a water contact angle, WCA ∼ 0°). The −OH bonds on the quartz surface facilitate the grafting of silicone oil onto the surface via hydrolysis and condensation reactions. , As a result of oil grafting, the hydrophilic quartz becomes hydrophobic with a nonadhesive behavior toward the water. The equilibrium water contact angle (WCA) of a 10 μL droplet on the oil-grafted surface is measured to be ∼107 ± 2°, as compared with the pristine quartz that exhibits a WCA of 58 ± 2° (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The spontaneous splitting of a droplet into multiple smaller droplets and integration with various sensing platforms has shown great potential, especially when integrated with optical spectroscopic studies. 16,18 However, most of these studies were carried out on flat surfaces and thus limit real-life applications where the surfaces are non-flat. To the best of our knowledge, no studies have been reported on curved surfaces such as contact lenses that utilized them for tear fluid splitting via adhesion differences of the substrate or employed optical sensing for tear fluid constituent measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-inspired surfaces are showing their potential in diverse areas including self-cleaning, water harvesting, water repellency, antibacterial, drag and friction reduction, anti-reflection, anti-corrosion, anti-fouling, structural coloration, thermal insulation, biosensing, etc. [13][14][15][16][17][18][19][20][21][22][23]…”
Section: Introductionmentioning
confidence: 99%